A Molecular Toolkit for the Functionalization of Titanium‐Based Biomaterials That Selectively Control Integrin‐Mediated Cell Adhesion. Issue 28 (6th June 2013) - Rechenmacher, Florian; Neubauer, Stefanie; Mas‐Moruno, Carlos; Dorfner, Petra M.; Polleux, Julien; Guasch, Judith; Conings, Bert; Boyen, Hans‐Gerd; Bochen, Alexander; Sobahi, Tariq R.; Burgkart, Rainer; Spatz, Joachim P.; et al.
Abstract: We present a click chemistry‐based molecular toolkit for the biofunctionalization of materials to selectively control integrin‐mediated cell adhesion. To this end, α5β1‐selective RGD peptidomimetics were covalently immobilized on Ti‐based materials, and the capacity to promote the selective binding of α5β1 was evaluated using a solid‐phase integrin binding assay. This functionalization strategy yielded surfaces with a nine‐fold increased affinity for α5β1, in comparison to control samples, and total selectivity against the binding of the closely related integrin αvβ3. Moreover, our methodology allowed the screening of several phosphonic acid containing anchoring units to find the best spacer–anchor moiety required for establishing an efficient binding to titanium and to promote selective integrin binding. The integrin subtype specificity of these biofunctionalized surfaces was further examined in vitro by inducing selective adhesion of genetically modified fibroblasts, which express exclusively the α5β1 integrin. The versatility of our molecular toolkit was proven by shifting the cellular specificity of the materials from α5β1‐ to αvβ3‐expressing fibroblasts by using an αvβ3‐selective peptidomimetic as coating molecule. The results shown here represent the first functionalization of Ti‐based materials with α5β1‐ or αvβ3‐selective peptidomimetics that allow an unprecedented control to discriminate between α5β1‐ and αvβ3‐mediated adhesions. The role of these two integrins in different biological events is still a matter of debate and is frequently discussed in literature. Thus, such bioactive titanium surfaces will be of great relevance for the study of integrin‐mediated cell adhesion and the development of new biomaterials targeting specific cell types. Abstract : Selective click : Based on a click chemistry derived molecular toolkit, an α5β1 integrin selective ligand was conjugated to a variety of alkyne‐modified spacer/anchor systems to investigate integrin binding on coated titanium (see scheme). The strategy was additionally extended to develop a phosphonate‐functionalized αvβ3‐selective ligand and selectivity in mediating integrin subtype specific cell adhesion was shown for both subtype selective ligands on TiO2 nanoarrays.